2017
DOI: 10.3758/s13423-016-1222-3
|View full text |Cite
|
Sign up to set email alerts
|

The goal of locomotion: Separating the fundamental task from the mechanisms that accomplish it

Abstract: Human locomotion has been well described but is still not well understood. This is largely true because the observable aspects of locomotion-neuromuscular activity that generates forces and motions-relate to both the task solution and the problem being solved. Identifying the fundamental task achieved in locomotion makes it possible to critically evaluate the motor control strategy used to accomplish the task goal. We contend that the readily observed movements and activities of locomotion should be considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This loss influences the strategies available for the use of limbs in walking since the limbs ultimately manage the interaction between the mass of the individual and the substrate. Defining the task of locomotion as managing the dynamic trajectory of the CoM through interaction of the mass and substrate (so that energy investment in the gait is optimized) recognizes what is ultimately accomplished, independent of how it is achieved—including the muscle activation patterns, the forces and torques produced, the work accomplished, and the energy expended (Croft, Schroeder, & Bertram, 2017).…”
Section: Limiting Loss As a Basis For Optimizing A Bipedal Walking Symentioning
confidence: 99%
“…This loss influences the strategies available for the use of limbs in walking since the limbs ultimately manage the interaction between the mass of the individual and the substrate. Defining the task of locomotion as managing the dynamic trajectory of the CoM through interaction of the mass and substrate (so that energy investment in the gait is optimized) recognizes what is ultimately accomplished, independent of how it is achieved—including the muscle activation patterns, the forces and torques produced, the work accomplished, and the energy expended (Croft, Schroeder, & Bertram, 2017).…”
Section: Limiting Loss As a Basis For Optimizing A Bipedal Walking Symentioning
confidence: 99%
“…In order to properly formalize the Sparrow and Newell construct, it is necessary to add to the concepts or organism and environment a clear definition of the task goal of locomotion and the process involved with the pressure to operate economically. In a previous article (Croft et al, 2017) we argue that the definition of the task in locomotion must be independent of the mechanisms/strategies that accomplish it, so that the problem(s) overcome with successful locomotion and the solutions utilized can be clearly distinguished. This allows the CNS selected solution to be evaluated in the context of the factors influencing the choices and the solution set of options properly mapped (in terms of both those selected and those avoided).…”
Section: How Should Locomotion Be Controlled and For What Purpose?mentioning
confidence: 99%
“…Having satisfied ourselves that definitions of the main constraints identified by Sparrow and Newell were possible, albeit dependent on a substantially different perspective of the task of locomotion (Croft et al, 2017), we sought a formalization of the suggested ‘pressure to operate economically.’ Based on the apparent influence of energetic cost derived from the studies discussed, we suggest that an assessment of energetic cost and the selection of less costly available options acts as the ‘pressure’ that guides the selection of movement strategy. This may occur in a broad range of motions but is particularly obvious in the energetically demanding context of locomotion.…”
Section: How Should Locomotion Be Controlled and For What Purpose?mentioning
confidence: 99%
“…Defining geometric features is relatively intuitive but defining which dynamic capabilities of the perceiver are important for reciprocal features of the environment requires a deeper understanding of the task. We have previously noted that even for a common behavior such as locomotion the functional task can be obscure, highlighting the importance of properly defining and understanding the task being undertaken (Croft et al, in press ).…”
Section: Introductionmentioning
confidence: 99%